2018
DOI: 10.1016/j.epsl.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature, salinity, and the carbonate system on Mg/Ca in Globigerinoides ruber (white): A global sediment trap calibration

Abstract: The Mg/Ca of planktic foraminifera Globeriginoides ruber (white) is a widely applied proxy for tropical and subtropical sea-surface temperature. The accuracy with which temperature can be reconstructed depends on how accurately relationships between Mg/Ca and temperature and the multiple secondary controls on Mg/Ca are known; however, these relationships remain poorly quantified under oceanic conditions. Here, we present new calibrations based on 440 sediment trap/plankton tow samples from the Atlantic, Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
176
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(203 citation statements)
references
References 48 publications
24
176
3
Order By: Relevance
“…The δ 18 O sw was calculated by converting monthly climatological salinity at 20‐m water depth (Levitus, ) using the regional surface water 18 O sw ‐salinity equation presented in section . Gray symbols show the Mg/Ca‐T global sediment trap data set for G. ruber compiled in Gray et al (). Black dashed line indicates the Mg/Ca‐T relationship determined by Gray et al () [Eq.S1: Mg/Ca = 1.26 exp(0.53T)], and the gray dashed line indicates the Mg/Ca‐T relationship determined by Anand et al () [ G. ruber (white) equation with fixed exponential constant, Mg/Ca = 0.449*exp(0.09*T)].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The δ 18 O sw was calculated by converting monthly climatological salinity at 20‐m water depth (Levitus, ) using the regional surface water 18 O sw ‐salinity equation presented in section . Gray symbols show the Mg/Ca‐T global sediment trap data set for G. ruber compiled in Gray et al (). Black dashed line indicates the Mg/Ca‐T relationship determined by Gray et al () [Eq.S1: Mg/Ca = 1.26 exp(0.53T)], and the gray dashed line indicates the Mg/Ca‐T relationship determined by Anand et al () [ G. ruber (white) equation with fixed exponential constant, Mg/Ca = 0.449*exp(0.09*T)].…”
Section: Resultsmentioning
confidence: 99%
“…Gray symbols show the Mg/Ca‐T global sediment trap data set for G. ruber compiled in Gray et al (). Black dashed line indicates the Mg/Ca‐T relationship determined by Gray et al () [Eq.S1: Mg/Ca = 1.26 exp(0.53T)], and the gray dashed line indicates the Mg/Ca‐T relationship determined by Anand et al () [ G. ruber (white) equation with fixed exponential constant, Mg/Ca = 0.449*exp(0.09*T)]. The solid black curve in each figure is the exponential Mg/Ca‐T relationship determined from the combined pink and white G. ruber data set from this study, with the 95% confidence intervals shown in gray shaded intervals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This novel approach has the advantage of potentially accounting for the variations in depth habitat and seasonality of foraminifera calcification between sites, assuming the δ 18 O of seawater is invariant. The approach is not without its own uncertainties however, and comparison of δ 18 O‐based and in situ temperatures can show offsets of up to 3 °C (Anand, Elderfield, et al, ; Gray et al, ). δ 18 O‐based temperatures are also poorly suited to multivariate calibrations considering that independent proxies for variables other than T either do not exist or have large uncertainties (Allen et al, ).…”
Section: Methodsmentioning
confidence: 99%